2022
DOI: 10.1093/ofid/ofac577
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen Cases of Daptomycin-Induced Eosinophilic Pneumonia in a Cohort of Patients Treated for Bone and Joint Infections: Proposal for a New Algorithm

Abstract: Background Daptomycin is increasingly used in the treatment of bone and joint infections (BJI) and may be responsible for daptomycin-induced eosinophilic pneumonia (DIEP), a potentially severe adverse drug reaction. The aim of this study was to describe DIEP in patients treated at a referral centre for the management of BJI, and to revisit current definitions of this disease. Method Patients treated from 01.01.2012 to 31.03.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Area under the concentration time curve (AUC) >939 mg.h/L is a similar measure used by Pham et al as a measure of the risk for DEP. They recommend targeting a therapeutic AUC range of 666 to 939 mg.h/L to minimize the risk of adverse effects [ 3 ]. Our patients had TCDD of 9.7 gm and 12.7 gm respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Area under the concentration time curve (AUC) >939 mg.h/L is a similar measure used by Pham et al as a measure of the risk for DEP. They recommend targeting a therapeutic AUC range of 666 to 939 mg.h/L to minimize the risk of adverse effects [ 3 ]. Our patients had TCDD of 9.7 gm and 12.7 gm respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the diagnostic criteria proposes a cut-off of 25% eosinophilia in BAL to be restrictive and invasive, in place of which a substitution with peripheral eosinophilia was suggested. A comparison of lung biopsy and BAL revealed eosinophilia in cases where BAL eosinophils were <25% implying that 25% might be too harsh a limit [ 3 ]. Kim et al stratified 77 cases of DEP reported on the Adverse Event Reporting System database into definite, probable, possible, and unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimmer et al [105] reported a similar case, in which the patient presented a daptomycin-induced AEP with sudden respiratory distress 9 days after a 3-day re-challenge of daptomycin, 2 weeks after priming. A third case by Pham et al reported an AEP upon re-exposure to daptomycin firstly occurred 6 months prior [75].…”
Section: Discussionmentioning
confidence: 99%
“…However, when the differential blood count was obtained, it showed significant eosinophilia of greater than 1000. Considering that the patient is on daptomycin and the findings of eosinophilia and chest imaging, our final diagnosis was daptomycin-induced eosinophilic pneumonia [ 5 , 6 ]. Daptomycin was stopped and steroids were added.…”
Section: Case Presentationmentioning
confidence: 99%